1999
DOI: 10.1136/gut.45.5.741
|View full text |Cite
|
Sign up to set email alerts
|

The preoperatively normal bile duct does not dilate after cholecystectomy: results of a five year study

Abstract: Background-The common hepatic duct (CHD) is commonly believed to dilate after cholecystectomy but previous studies have either not measured CHD diameter preoperatively or the follow up period is short. Aims-To measure CHD diameter before and after cholecystectomy. Methods-Patients undergoing (open)cholecystectomy and operative cholangiography had ultrasonographic measurement of CHD diameter before, and three and six months, and one and five years after cholecystectomy. The normal duct diameter was considered t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
7

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 13 publications
0
17
0
7
Order By: Relevance
“…(For proximal common bile duct measurements, there was no interaction between age and cholecystectomy status; therefore, we pooled the data for the regression analysis) which is substantially lower than the mean difference we detected. Authors of studies that had relatively short follow-up time periods concluded that there was no postcholecystectomy dilatation [12,13], while studies that followed patients for longer durations of time after surgery revealed a trend towards dilatation [3,10,11]. It is difficult to interpret results of studies that followed patients for a prolonged period of time because the CBD diameter increases with age [14].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…(For proximal common bile duct measurements, there was no interaction between age and cholecystectomy status; therefore, we pooled the data for the regression analysis) which is substantially lower than the mean difference we detected. Authors of studies that had relatively short follow-up time periods concluded that there was no postcholecystectomy dilatation [12,13], while studies that followed patients for longer durations of time after surgery revealed a trend towards dilatation [3,10,11]. It is difficult to interpret results of studies that followed patients for a prolonged period of time because the CBD diameter increases with age [14].…”
Section: Discussionmentioning
confidence: 89%
“…Therefore, results from these studies may underestimate or fail to detect biliary dilatation. For example, studies that employed this before-andafter design have estimated a mean increase in post-cholecystectomy biliary duct dilatation (0.6 mm) [3,10,11] Fig. 1 Graphical display of the common bile duct diameter by age and cholecystectomy status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ulteriormente, en 1999 se realizó un estudio con 59 pacientes seguidos con ET antes, a los 3 y 6 meses y en 1 y 5 años después de la colecistectomía abierta. Encontraron que el diámetro promedio antes de la cirugía fue de 3,43 mm y a los 5 años de seguimiento fue de 3,96 mm (margen de error de 1 mm en la medición), pero no hubo diferencia estadística (47)(48)(49).…”
Section: Edad De Los Pacientes (Años)unclassified
“…Most patients being investigated for SOD have had their gallbladder removed and in the past it was accepted that it was normal for a post-cholecystectomy CBD to be 2-3 mm dilated. However, in a cohort of 59 patients, Majeed et al [11] found no difference between pre-and post-cholecystectomy CBD diameter. As the upper limit of normal for CBD diameter is 7 mm, a cut off of 12 mm potentially leaves a large number of patients misdiagnosed.…”
Section: Classification Of Sodmentioning
confidence: 99%